The Effect of Socio-Economic Characteristics on the Income Level of Women Vegetable Traders: (Case Study at Gemba Market, Waimital Village, Kairatu District, West Seram District - Meiska Alfia Girsang; Stephen Frans William Thenu; Junianita Sopamena (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine the socio-economic characteristics of traders in the Gemba market, Kairatu District, West Seram Regency. The research was conducted at the Gemba market for 1 month April 2023. The method used in this study used a purposive sample. The sample will be taken with the consideration that the sample size represents the population. Based on the results of the study, it was shown that most of the housewives who were still actively working were 13 people aged between 40-50 years, however, there were 8 respondents aged 29-39 who worked as vegetable traders. The level of education explained that the education level of the women who were respondents varied from those who did not attend school as much as 1 person (3.33%), there were 10 people who graduated from elementary school (33.33%), and junior high school as many as 5 people (16.68), the height the percentage of respondents whose education only reached senior high school (SMA) was 13 people (43.33%), and there were 1 D3 graduate (3.33), who worked as a vegetable seller, the third number of dependents, that the number of family dependents on vegetable traders who have the least number of dependents of family members is 3-4 people as many as 25 people (83.33%), then family dependents of >4 people are 5 people (16.67%). The length of trading that the length of business of vegetable traders in Gemba Market, Kairatu sub-district varies from 1-10 years as many as 11 people or 36.67% where these traders have just started their business. While the majority of vegetable traders are from 11-20 years old or as many as 14 people or 46.67%. Kairatu sub-district varies from 1-10 years as many as 11 people or 36.67% where these traders have just started their business. While the majority of vegetable traders are from 11-20 years old or as many as 14 people or 46.67%. Kairatu sub-district varies from 1-10 years as many as 11 people or 36.67% where these traders have just started their business. While the majority of vegetable traders are from 11-20 years old or as many as 14 people or 46.67%.